Effect of supplementation of vitamin E, copper and zinc on the in vitro phagocytic activity and lymphocyte proliferation index of peripartum Sahiwal (Bos indicus) cows. Issue 2 (31st January 2012) - Dang, A. K.; Prasad, S.; De, K.; Pal, S.; Mukherjee, J.; Sandeep, I. V. R.; Mutoni, G.; Pathan, M. M.; Jamwal, M.; Kapila, S.; Kapila, R.; Kaur, H.; et al.
Summary To study the effect of vitamin E (VE), copper (Cu) and zinc (Zn) supplementation on the in vitro phagocytic activity (PA) and lymphocyte proliferation response (LPR) of blood neutrophils and lymphocytes, thirty Sahiwal pregnant cows (six in each group) in their late gestation at 30 days before the expected date of calving were selected from the NDRI experimental herd and supplemented with various micronutrients from 30 days before calving to 45 days after calving. Cows were supplemented individually with VE (1000 IU/cow/day), Cu (20 ppm/cow/day) and Zn (80 ppm/cow/day) and also with a combination of VE, Cu and Zn to study cumulative effect of all micronutrients. One group without any supplementation acted as a control. Blood neutrophils and lymphocytes were isolated and studied for their PA and LPR. Supplementation of micronutrients like VE, Cu, Zn and a combination of all these nutrients significantly (p < 0.01) increased the PA of experimental cows as compared to control (unsupplemented) cows during the pre‐partum period. During post‐partum, all the micronutrients (VE, Cu, Zn and their combination) showed a significant (p < 0.01) increase in the PA of experimental cows as compared to control cows. Of all the groups, significant (p < 0.01) and maximum PA was observed in the combination group followed by Zn‐supplemented group during both the pre‐ and post‐partum period. A significant (p < 0.01) increase in LPR of B lymphocytes was observed in combination‐supplemented group during the pre‐partum period and during both the pre‐ and post‐partum period in the Cu‐supplemented group.